2004
DOI: 10.1016/j.jacc.2003.11.065
|View full text |Cite
|
Sign up to set email alerts
|

Impaired intravascular triglyceride lipolysis constitutes a marker of clinical outcome in patients with stable angina undergoing secondary prevention treatment

Abstract: The current study establishes that delayed intravascular TG lipolysis is a strong and independent predictor of evolution to severe angina among patients undergoing secondary prevention therapy of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 25 publications
0
15
0
10
Order By: Relevance
“…Artificial lipid nanoemulsions can be used as probes to detect genetically inherited alterations or evaluate pharmacological, nutritional and other interventions on lipoprotein metabolism (1)(2)(3)(4). A single preparation of these artificial nanoemulsions can be injected into several patients for plasma kinetic studies, whereas only the autologous native lipoprotein can be injected into subjects, due to the risk of infection or immunological reactions resulting from the use of heterologous lipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial lipid nanoemulsions can be used as probes to detect genetically inherited alterations or evaluate pharmacological, nutritional and other interventions on lipoprotein metabolism (1)(2)(3)(4). A single preparation of these artificial nanoemulsions can be injected into several patients for plasma kinetic studies, whereas only the autologous native lipoprotein can be injected into subjects, due to the risk of infection or immunological reactions resulting from the use of heterologous lipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…Lipoproteins can be modeled by artificially made lipid emulsions [3][4][5][6][7]. We have shown that nanoemulsions (LDE) roughly resembling the lipidic structure of LDL particles, as described above, but made without protein, are taken-up by LDL receptors [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, cholesteryl esters clearance was the only independent predictor of the presence of CAD. In another study from our laboratory (30), it was also shown that a slower remnant removal was related with worse subsequent clinical evolution of postmyocardial infarction patients, as followed by an average period of 4.5 years.…”
Section: Figurementioning
confidence: 77%